2019
DOI: 10.1111/1745-9125.12214
|View full text |Cite
|
Sign up to set email alerts
|

Development of impulsivity and risk‐seeking: Implications for the dimensionality and stability of self‐control*

Abstract: In Gottfredson and Hirschi's self‐control theory, introduced in 1990, they contend that self‐control is a unidimensional construct that develops early in childhood and remains stable throughout the life span. According to findings reported in recent research, however, these arguments are now being challenged, with scholars pointing to ways in which self‐control may be multidimensional in nature and may change beyond the period of alleged stabilization. In this study, we draw on Steinberg's dual systems model, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 53 publications
2
60
0
1
Order By: Relevance
“…The data used for our study, however, permit a partial assessment of this question. Self‐control has been measured in a variety of ways, but most scholars have emphasized indicators of impulsivity and a sensation‐seeking (Burt et al, 2014; Forrest et al, 2019; Gottfredson & Hirschi, 1990). We cannot document changes in impulsivity, but the MTF data used for our study provide information on preferences for risky and dangerous activities, which are commonly used to identify those more prone to sensation‐seeking.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The data used for our study, however, permit a partial assessment of this question. Self‐control has been measured in a variety of ways, but most scholars have emphasized indicators of impulsivity and a sensation‐seeking (Burt et al, 2014; Forrest et al, 2019; Gottfredson & Hirschi, 1990). We cannot document changes in impulsivity, but the MTF data used for our study provide information on preferences for risky and dangerous activities, which are commonly used to identify those more prone to sensation‐seeking.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Online as well as offline deviance can be 'delightful' (Katz, 1988: 312). From a regulatory perspective, however, these features serve to degrade young people's finite resources of self-regulation and impulse control (Forrest et al, 2019). Digital drift for many young people therefore becomes extremely easy to do (Goldsmith and Brewer, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Research yields general support for the proposition that individuals with low self-control will be disproportionally involved in crime (Pratt and Cullen 2000; Vazsonyi, Mikuška, and Kelley 2017) and a host of analogous behaviors (Arneklev et al 1993; Paternoster and Brame 2000; Reisig and Pratt 2011). Regarding the stability hypothesis, extant research reveals that while self-control is found to be relatively stable for many individuals, relative changes in self-control do occur for a nontrivial portion of the population, especially among studies with longer follow-up periods (Burt et al 2006; Forrest et al 2019; Hay and Forrest 2006; Na and Paternoster 2012; Turner and Piquero 2002).…”
Section: Self-control Theorymentioning
confidence: 99%